Integral characteristics of induction loop located overthin conducting layer - Portnov, V.S.; Reva, N.V.; Onishchuk, V.I.; Li, E.S. (KSU Publ., 2018)
In the general form, the integral principle of electromagnetic soundings was developed, based on an analysis of generalized regularities of electromagnetic fields in the Earth, as spatial electric circuits. The mentioned approach determines the basic contours of a possible new direction in the development of applied electrometry. The problem of the dynamic interaction of an ungrounded loop, that is powered by a harmonic current, with a thin conducting bed, was solved. Analytic relationships that describe the dynamic increments of the active resistance and loop inductance as a function of frequency were obtained as a result of solving this problem. The asymptotic analysis of the obtained relations in the intervals of asymptotically low and high frequencies was performed, and on the basis of received results algorithms for interpreting the experimental frequency dependences of integral characteristics of the induction loop were developed. The performed fundamental developments were tested on experimental data of laboratory measurements of the frequency dependences of the increment of the active resistance and inductance of loops located above the conducting bed and on its surface. A full confirmation of the theoretical developments and in formativeness of the integral parameters of induction loops was obtained.
Жұқа өткізгіш қабаттың үстінде орналасқан индукциялық ілгектің интегралдық сипаттамалары
Интегральные характеристики индукционной петли, расположенной над тонким проводящим слоем
Keywords: electrical exploration; induction loop; active resistance; inductance; longitudinal conductivity; conductive layer; magnetic flux; frequency; integrated characteristics; electromagnetic sounding